(untitled) (Web of Teachers: Inderscience Research, 2026)
This study examines the development of an individualized exercise system based on students’ linguistic errors in native language lessons. The research addresses the need for differentiated instruction that responds directly to learners’ specific grammatical, lexical, and syntactic difficulties. A mixed-methods approach was employed, including classroom observation, diagnostic assessment of linguistic errors, and the implementation of a structured system of individualized exercises. The findings indicate that targeted practice based on error analysis significantly improves students’ language accuracy, comprehension, and overall communicative competence. The study emphasizes the pedagogical importance of transforming errors into diagnostic tools that inform instruction and promote personalized learning pathways in language education.